Neutrophil-to-Lymphocyte Ratio in Adult Patients with Anemia: A Hospital-Based Cross-Sectional Study - Manandhar, Nilu; Bhattarai, Kushal; Bhandari, Krishant (Journal of Karnali Academy of Health Sciences, 2023)
Background: Neutrophil-to-lymphocyte ratio, a well-defined marker of immunity, is raised in many conditions which are characterized by abnormal inflammatory and immunological responses. Anemia of chronic disease, the most prevalent type in hospitalized patients, is a dominant clinical picture in protracted stimulation of immunity. This study aimed to assess the neutrophil-to-lymphocyte ratio in adult participants with anemia and to compare of the ratio with non-anemic participants. Methods: In a cross-sectional study conducted in the Department of Clinical Physiology of Karnali Academy of Health Sciences, Teaching Hospital, Jumla, Karnali Province, Nepal, in the months of August, 2023, data on clinico-demographic variables were retrieved from the laboratory information system of hospital records of February–March, 2023. From the hematological parameters retrieved, the status of anemia and the neutrophil-tolymphocyte ratio were calculated. Results: After scrutiny of the laboratory records of 1421 adult patients, with 69.7% (N=990) female, the prevalence of anemia was 12.4% (N=176) and the median neutrophil-to-lymphocyte ratio was 2.21 (IQR: 1.41–3.75). The median neutrophil-to-lymphocyte ratio was significantly greater in the anemic participants among the overall (p<0.001) participants and across the subgroups of gender (p<0.001) and age (p<0.05). Conclusion: The neutrophil-to-lymphocyte ratio was significantly greater in the adult anemic than in the nonanemic participants. To this end, further studies assessing the association of this ratio with the various clinical aspects of anemia, such as subtypes, severity, course, prognosis and treatment responses are needed.